Circular pOlyethylene drape in preVEntion of suRgical site infection (COVER trial): study protocol for a randomised controlled trial. Issue 1 (22nd January 2020) - Yoo, Ri Na; Kim, Hyung Jin; Lee, Jae Im; Kang, Won-Kyung; Kye, Bong-Hyeon; Kim, Chang Woo; Bae, Sung Uk; Nam, Soomin; Kang, Byung Mo
Abstract : Introduction: Surgical site infection (SSI) after abdominal surgery remains a significant cause of morbidity and is associated with an increased socioeconomic burden and a reduced quality of life. Circular wound protectors have been expected to reduce the risk of SSI, but previous studies reported conflicting results on their protective effects. The purpose of this study was to evaluate the efficacy of circular wound protectors in reducing SSI in open abdominal surgery. Methods and analysis: The circular pOlyethylen drape in preVEntion of suRgical site infection (COVER) trial investigates whether the application of a dual-ring circular plastic wound protector reduces the rate of SSI in patients undergoing elective or emergent open abdominal surgery related to the gastrointestinal tract, regardless of the type of wound classified by the Centers for Disease Control. The COVER trial is a multicentre, randomised controlled clinical trial with two parallel arms—one using a dual-ring wound protector with circular polyethylene drape and the other using conventional surgical dressing gauze. The primary outcome will measure the rate of SSI within 30 days after surgery in two groups. Statistical analysis of the primary end point will be based on the intention-to-treat population. The sample size was determined to achieve a study power of 80% with 95% two-sided confidence limits. Considering a dropout rate of up to 5%, a total of 458 patients, 229 patients in each group, will be enrolled in this study. Ethics and dissemination: The trial protocol and informed consent document have been reviewed and approved by the institutional review board at each participating centre. Written informed consent will be obtained from each study participant. The clinical outcomes of this trial will be submitted to an international peer-reviewed journal and presented at international conferences. Trial registration number: NCT 03170843.